DAMPAK SISTEM KEBUT SEMALAM TERHADAP TINGKAT PLAGIARISME TUGAS MAHASISWA IKIP SILIWANGI - Widdy Rahmah Umar; Amalia Siddiqa Rahayu; Dida Firmansyah (IKIP Siliwangi, 2018)
The purpose of this research was to improve the skills of students of IKIP Bandung Siliwangi to better critical thinking. Speeding system overnight is a behavior that is done by students, these systems have become habits of college students to get results more easily and the task is resolved. Students studying with the speeding system overnight give bad impact towards physical and brain, which are constantly forced to learn all the intended subjects. But in fact, there are many students who are not yet able to apply independent study well. In the set time among students is a difficult thing to life. Especially in a set time, to complete the task quickly. So, raises the speeding system overnight behavior that will be the Act of plagiarism. Learning style is the way taken by each person in absorbing new information. As for the type of student learning style can be distinguished into three types namely (1) the Visual meaning of learning styles by using the sense of sight, (2) Auditorial means learning styles by using the senses of hearing, and (3) Kinesthetic means learning style receiving a lesson which is done with motion.